Switchable multiwavelength Brillouin-Raman fiber laser utilizing an enhanced nonlinear amplifying fiber loop design - Mamdoohi, Ghazaleh; Sarmani, Abdul Rahman; Abu Bakar, Muhammad Hafiz; Mahdi, Mohd Adzir (IEEE, 2018)
We propose and demonstrate a new multiwavelength Brillouin-Raman fiber laser with switchable 10 and 20 GHz spacing. This is achieved by proper adjustments of optical coupling ratios that are incorporated in the design that consists of an enhanced nonlinear amplifying fiber loop. By utilizing a 50/50 coupler, 443 flat amplitude channels with 10 GHz spacing is realized. On the other hand, a 99/1 coupler is feasible for 20 GHz spacing that yields 215 lasing lines. In both cases, the average optical signal-to-noise ratios (OSNR) are 16.5 dB (50/50 coupler) and 24 dB (99/1 coupler). Wide multiwavelength bandwidth, flexible wavelength spacing, and high number of channels with excellent OSNRs are achieved using only a single Raman pump unit through a simple construction.